THE EFFECT OF EMPLOYEE RETENTION AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE WITH TURNOVER INTENTION AS AN INTERVENING VARIABLE (Study on employees of PT. Pos Indonesia Tebing Tinggi Branch) - Puspita Sari; Igles Natalia; Dedy Dwi Arseto; Nursaimatussaddiyah Nursaimatussaddiyah (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine The Effect Of Employee Retention And Organizational Commitment On Employee Performance With Turnover Intention As An Intervening Variable (Study on employees of PT. Pos Indonesia Tebing Tinggi Branch). The research method used is a quantitative method using the help of Smart PLS version 3.0 which was collected from the results of distributing questionnaires. The analytical method used in this research is to use instrument tests, namely validity and reliability tests. measurement model (outer model), namely the validity test, reliability test, then the structural model (inner model) including: coefficient of determination/r-square (r2), goodness of fit model and hypothesis testing with the t-statistic test and indirect influence test ( indirect effect). The results of Smart PLS 3.0 in this research are that organizational commitment in this research does not have a significant effect on employee performance. Organizational commitment in this research has a significant effect on turnover intention. Employee retention in this study did not have a significant effect on employee performance. Employee retention has a significant effect on turnover intention. Turnover intention in this research has a significant influence on employee performance. Turnover intention is able to mediate or intervene in the influence of organizational commitment on employee performance. Turnover intention cannot mediate the effect of employee retention on employee performance. Keywords: Organizational Commitment, Employee Retention, Turnover Intention, Employee Performance